The Laozi and the Cosmogonic Turn in Classical Chinese Philosophy - Perkins, Franklin (2017)
In the past several decades, our understanding of the Laozi has been revolutionized by the discovery of new textual materials. While research has focused on various manuscript copies, the discovery of other cosmogonic texts dated to the late fourth century BC indicate that the Laozi was not as unique as it once seemed. Taken together, these texts show a radical shift in philosophical orientation occurring by the late 4th century BC, a change toward concerns with cosmogony and accounts of human beings as merely one part of the natural world. The goal of this paper is to analyze the various elements of this shift, using the Taiyi Sheng Shui 太一生水 (Great One Generates Water), Hengxian 恆先 (Constancy First), and Fan Wu Liu Xing 凡物流形 (All Things Flow into Form), along with the Laozi bamboo strips found at Guodian. The first section examines the commonalities between the various cosmogonies; the second places cosmogony in the context of other distinctive concerns that the texts share, turning toward the implications of the cosmogonies for human action. The final section examines one of the fundamental points on which the texts disagree.